Preparation method of layered nickel-cobalt double hydroxide (NiCo-LDH) nanosheet
NiCo-LDH nanosheets were prepared in sodium chloride and sodium acetate solution by cathode glow discharge electrolysis, which solved the problems of complex preparation methods, high cost and contamination in the prior art, and achieved efficient and environmentally friendly nanomaterial preparation. It has simple process flow and good morphological control.
Patent Information
- Application Number
- CN202411089150.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-17
AI Technical Summary
The existing NiCo-LDH nanosheet preparation methods are complex, the conditions are harsh, the production costs are high, and secondary pollution is generated, making it difficult to achieve controllable structure and morphology.
Using cathode glow discharge electrolysis method, a high-voltage DC power supply is used to apply voltage in a mixed solution of sodium chloride and sodium acetate. Through the electrochemical reaction of cathode platinum needle and nickel-cobalt alloy sheet, active species are generated and NiCo-LDH nanosheets are formed. , and the preparation is achieved by magnetic stirring and distilled water.
The preparation of NiCo-LDH nanosheets with mild conditions, controllable reactions and no by-products was realized, which reduced energy consumption and environmental pollution, and improved the purity and morphological control of the product.
Smart Images

Figure CN119144967A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, in particular to a method for preparing layered nickel cobalt double hydroxide (NiCo-LDH) nanosheets. Background Art
[0002] Layered nickel cobalt double hydroxide (NiCo-LDH) is a type of two-dimensional anionic layered compound composed of two metal hydroxides, Ni and Co. It has a hydrotalcite-like lamellar structure, which consists of positively charged lamellar layers and interlayer anions. 2+ 、Co 3+ ) is located at the center of the octahedron and is connected to the surrounding OH - Ions are bound together by coordination bonds to form a lamellar main structure; anions fill the interlayer gaps to balance the charge; and solvent water molecules fill the remaining gaps. This unique two-dimensional stacking structure not only makes NiCo-LDH have good biocompatibility, ion exchangeability, and alkali and salt resistance, but also gives NiCo-LDH an ultra-high specific surface area. Therefore, NiCo-LDH has broad application prospects in the fields of biomedicine, energy conversion and storage, sensors, and environmental protection.
[0003] At present, the main methods for preparing NiCo-LDH include coprecipitation, hydrothermal method, calcination recovery method, etc. The essence of coprecipitation is that the precursor metal salt (sulfate, nitrate and chloride, etc.) and alkali (NaOH, KOH, NH3·H2O, urea, ethanolamine, hexamethylenetetramine, etc.) undergo coprecipitation reaction to generate the target product LDHs. However, in the coprecipitation process, the bimetallic ion Ni needs to be strictly controlled. 2+ / Co 3+The ratio of , accurately adjust the pH of the solution (to ensure that the metal ions in the solution can be completely precipitated); at the same time, adjust the reaction temperature (80 ~ 120 ℃), and add stabilizers (PVP, CTAB, SDS, etc.) to promote the crystal growth of NiCo-LDH. The hydrothermal method is to use a water-alcohol mixture as a medium in a closed high-pressure reactor, react at high temperature (> 120 ℃) (> 10h), and promote the precipitation of metal salts in an alkaline solution to generate NiCo-LDH particles of uniform size. However, the hydrothermal reaction in a high-temperature environment is very complex, and it is difficult to accurately control the factors affecting the reaction. The roasting recovery method is to add the roasting product of NiCo-LDH to a solution containing the target anion, and restore the NiCo-LDH structure through lattice replacement of similar ions. However, this method has a narrow scope of application (more suitable for the synthesis of NiCo-LDH with larger anions such as organic acid salts and oxygen-containing acid salts), and high-temperature roasting is easy to generate amorphous phase substances. Although the above methods have made great achievements in the preparation of NiCo-LDH, and some methods (co-precipitation method) have been produced on a large scale, there are still some shortcomings. The main manifestations are: expensive raw materials, harsh conditions, complex processes, and long reaction times; the above methods are strongly dependent on toxic chemical reagents, including precursor metal salts, alkali sources, stabilizers, surfactants, organic solvents, etc., which are prone to secondary pollution; due to the many factors that affect the growth of NiCo-LDH grain size (proportion and concentration of precursor salts, solution pH, reaction temperature, reaction time, etc.), the correlation between the structure and morphology of NiCo-LDH and the reaction conditions is extremely complex, making it difficult to achieve controllable preparation of NiCo-LDH. Therefore, it is of great significance to develop a new method for preparing nano-NiCo-LDH with simple process, controllable morphology, and green environmental protection.
[0004] Cathodic glow discharge electrolysis (CGDE) is a new type of electrochemical method for generating nonequilibrium low-temperature plasma in aqueous solution. Different from ordinary electrolysis, CGDE is based on the principle of tip discharge. In the electrolyte solution, a metal sheet (rod) is used as the anode and a platinum needle made by a special process is used as the cathode. When a sufficiently high voltage is applied, a glow is emitted between the cathode platinum needle and the surrounding electrolyte to form a plasma, and HO·, O·, H·, HO2·, H2O2, e aq - OH - Based on the strong oxidizing properties of OH·, O·, H2O2 and H·, e aq -Due to its strong reducing property and emission spectrum characteristics, CGDE has been widely used in wastewater treatment, organic synthesis, polymer preparation, spectral analysis and other fields. At the same time, as a green nanomaterial preparation technology, CGDE has the advantages of simple steps (one-step method), mild conditions (no high temperature required), controllable reaction, few by-products, and low energy consumption (power <100W). At present, there are many reports on CGDE in the preparation of precious metal nanoparticles (Ag, Au), metal oxides (ZnO, Fe3O4, TiO2, Mn3O4), and metal hydroxides (Mg(OH)2, Ni(OH)2, Co(OH)2), but there are no reports on its use in the preparation of NiCo-LDH nanomaterials. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing NiCo-LDH nanosheets based on the advantages of cathode glow discharge electrolytic plasma, in view of the defects of the existing NiCo-LDH nanosheets, such as complex preparation process, harsh conditions, high production cost, secondary pollution and the like.
[0006] In order to achieve the above purpose, the technical solutions provided are as follows:
[0007] A method for preparing NiCo-LDH nanosheets, characterized in that it comprises the following steps:
[0008] Step 1: Use a high-voltage DC power supply to provide power, the cathode is a homemade platinum electrode, the anode is a nickel-cobalt alloy sheet, the electrolyte is a mixed solution of sodium chloride and sodium acetate, wherein sodium acetate is used as a stabilizer to control the morphology of NiCo-LDH, and a stabilizing resistor is added to the circuit;
[0009] Step 2: Use a DC high voltage power supply to apply a sufficiently high voltage between the electrodes, and the cathode platinum needle will produce a tip discharge, thereby forming a stable glow;
[0010] Step 3: The nickel-cobalt alloy sheet of the anode continuously produces Ni in the solution through the anode dissolution process. 2+ and Co 2+ , the cathode plasma-liquid interface produces active species such as e aq - , H·, HO·, H2O2, and then secondary reactions occur to produce OH - ;
[0011] Step 4: Use a magnetic stirrer to continuously stir and discharge for a period of time to obtain a blue-green turbid liquid;
[0012] Step 5: Centrifuge the blue-green turbid liquid, wash it with distilled water and anhydrous ethanol for several times, dry it, and grind it to obtain a blue-green solid powder, which is NiCo-LDH.
[0013] Preferably, in step 1, the electrolyte is 200 mL of 2 g / L sodium chloride solution, and the stabilizer is 0.5 to 1.5 g of sodium acetate added to 200 mL of the electrolyte.
[0014] Preferably, in step 1, the cathode is a platinum wire with a length of 20 mm and a diameter of 1 mm sealed in a quartz tube; the anode is a nickel-cobalt alloy sheet Ni50Co50 with a length of 6 cm, a width of 1 cm and a thickness of 5 mm; the positive and negative electrodes are inserted 3 cm below the liquid surface.
[0015] Preferably, in step 1, the surface oxide film of the anode nickel-cobalt alloy sheet must be removed before use, firstly polished with 1000-grit sandpaper, and then cleaned with an ultrasonic cleaner.
[0016] Preferably, in step 1, a 1-5 kΩ ballast resistor is connected between the negative electrode of the power supply and the cathode of the platinum needle.
[0017] Preferably, in step 2, when the voltage is 500-550V and the current is 50-70mA, the cathode generates tip discharge to form a stable plasma.
[0018] Preferably, in step three, during the discharge process, the reaction temperature is maintained at 70-80°C.
[0019] Preferably, in step 4, the magnetic stirrer continuously stirs the solution at 120-150 r / min to maintain the uniformity of the solution, and the glow discharge electrolysis is continued for 1.0 h.
[0020] Preferably, in step five, the speed of the centrifuge during sample processing is 8000-10000 r / min, and the sample is vacuum dried at 60°C.
[0021] A preparation device for NiCo-LDH nanosheets comprises a reaction container 5 and a DC voltage-stabilized current-constant power supply 1, wherein the DC voltage-stabilized current-constant power supply 1 is placed on the top of the reaction container 5, an electrolyte solution 8 is contained in the reaction container 5, a positive power supply electrode 2 of the DC voltage-stabilized current-constant power supply 1 is connected to a nickel-cobalt alloy sheet anode 9 through a wire, the nickel-cobalt alloy sheet anode 9 extends from the top of the reaction container 5 into the electrolyte solution 8 in the reaction container 5, a negative power supply electrode 3 of the DC voltage-stabilized current-constant power supply 1 is connected to a loop resistor 4 and a platinum needle cathode 10 through a wire, the platinum needle cathode 10 extends from the top of the reaction container 5 into the electrolyte solution 8 in the reaction container 5; the DC voltage-stabilized current-constant power supply 1, the loop resistor 4, the nickel-cobalt alloy sheet anode 9, the electrolyte solution 8 and the platinum needle cathode 10 constitute a discharge circuit.
[0022] The exterior of the reaction container 5 is a hollow structure, and condensed water is contained in the interior of the hollow structure. A condensed water inlet 12 is provided on the bottom side wall of the hollow structure, and a condensed water outlet 13 is provided on the upper side wall of the reaction container 5 .
[0023] The condensed water inlet 12 and the condensed water outlet 13 are opened on two opposite side walls of the reaction container 5 .
[0024] A magnetic stirrer 15 is installed at the bottom of the reaction container 5 , and a magnetic stirrer 14 of the magnetic stirrer 15 extends from the bottom of the reaction container 5 into the electrolyte solution 8 inside the reaction container 5 .
[0025] A cover 6 is disposed on the top of the reaction container 5 , and a vent hole 7 is disposed on the cover 6 .
[0026] The cover 6 is made of polytetrafluoroethylene.
[0027] The reaction container 5 is a homemade 250 mL constant temperature container.
[0028] The beneficial effects of the present invention are:
[0029] 1. During the CGDE process, the active species generated at the cathode can be partially converted into OH - And it is used as an alkali source for the preparation of NiCo-LDH.
[0030] 2. The anode NiCo alloy electrode gradually corrodes and dissolves during the interfacial electrochemical reaction to provide Ni 2+ and Co 2+ Metal ions.
[0031] 3. Sodium chloride electrolyte provides intercalated Cl-, and sodium acetate is added as a stabilizer. By precisely controlling influencing factors such as discharge voltage, discharge time, alloy composition, electrolyte type and concentration, OH - The metal ions are released slowly and orderly in a controllable manner, and then through the plasma-liquid synergistic effect, high-purity and good-morphology layered nickel cobalt double hydroxide (NiCo-LDH) nanosheets are prepared in one step.
[0032] 4. Compared with other NiCo-LDH preparation methods, the advantages of CGDE technology are: simple equipment and mild conditions (no reactor is required, reaction time is 0.5-2h at 70-80℃); short process flow and controllable reaction (one-step preparation, controlling the morphology of the material by controlling the influencing factors); efficient reaction and green environmental protection (no need to add additional reducing agents, oxidizing agents, alkali sources and metal precursor salts during the entire preparation process), no by-products; raw materials (alloy sheets, abundant reserves) are non-toxic and easy to obtain, and low energy consumption (power is less than 60W). BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The present invention provides a schematic diagram of a device for preparing NiCo-LDH nanosheets by cathode glow discharge electrolysis; wherein: 1. a DC voltage and current stabilized power supply; 2. a positive electrode of the power supply; 3. a negative electrode of the power supply; 4. a loop resistor; 5. a reaction container; 6. a polytetrafluoroethylene cover; 7. an exhaust hole; 8. an electrolyte solution; 9. a nickel-cobalt alloy sheet anode; 10. a platinum needle cathode; 11. a glow discharge plasma; 12. a condensed water inlet; 13. a condensed water outlet; 14. a magnetic stirrer; and 15. a magnetic stirrer.
[0034] Figure 2 It is a CGDE emission spectrum diagram of the preparation of NiCo-LDH nanosheets provided by the present invention; wherein, the discharge voltage is 500V, the electrolyte is 200mL 2g / L sodium chloride solution, and 1.0g sodium acetate is added;
[0035] Figure 3 This is a graph showing the pH change of a solution for preparing NiCo-LDH nanosheets provided by the present invention; wherein the discharge voltage is 500V, the electrolyte is 200mL of a 2g / L sodium chloride solution, and 1.0g of sodium acetate is added;
[0036] Figure 4 This is an infrared spectrum of the NiCo-LDH nanosheet provided by the present invention; wherein the discharge voltage is 500V, the electrolyte is 200mL 2g / L sodium chloride solution, and 0.5-1.5g sodium acetate is added;
[0037] Figure 5 The XRD spectrum of the NiCo-LDH nanosheet provided by the present invention is as follows; wherein the discharge voltage is 500V, the electrolyte is 200mL of 2g / L sodium chloride solution, and 0.5-1.5g of sodium acetate is added;
[0038] Figure 6 The SEM morphology of the NiCo-LDH nanosheet provided by the present invention is shown in Figure 1; wherein, a is a discharge voltage of 500 V, the electrolyte is 200 mL of a 2 g / L sodium chloride solution, and 0.5 g of sodium acetate is added; b is a discharge voltage of 500 V, the electrolyte is 200 mL of a 2 g / L sodium chloride solution, and 1.0 g of sodium acetate is added; c is a discharge voltage of 500 V, the electrolyte is 200 mL of a 2 g / L sodium chloride solution, and 1.5 g of sodium acetate is added;
[0039] Figure 7 This is the EDS spectrum of the NiCo-LDH nanosheet provided by the present invention; wherein, the discharge voltage is 500V, the electrolyte is 200mL of 2g / L sodium chloride solution, and 1.0g of sodium acetate is added. DETAILED DESCRIPTION
[0040] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] In a 250mL temperature-controlled reactor, 200mL of 2g / L sodium chloride solution was added as the electrolyte, and 0.5g of sodium acetate was added to the solution as a stabilizer. The cathode was a homemade platinum electrode (a platinum wire with a length of 20mm and a diameter of 1mm sealed in a quartz tube). The anode was a nickel-cobalt alloy sheet (the surface oxide film was polished with sandpaper, and then ultrasonically washed in anhydrous ethanol and deionized water for 10min each). In order to maintain the uniformity of the solution, the solution was continuously stirred at 120r / min with a magnetic stirrer. When the voltage was 500V, the current was 53mA, and the external resistance was 2kΩ, the solution temperature was maintained at 70℃, the cathode produced a glow, and a stable glow discharge plasma was formed. During the discharge process, the anode nickel-cobalt alloy sheet was continuously consumed, and a blue-green precipitate gradually appeared in the colorless solution. After continuous discharge for 1h, a blue-green NiCo-LDH product was obtained. The turbid solution was allowed to stand for 24 hours, then centrifuged at 8000 r / min for 10 minutes. The obtained product was washed with distilled water and anhydrous ethanol for several times to remove the electrolyte soluble salt, and finally vacuum dried at 60°C to constant weight and ground to obtain the target product. Its infrared, XRD and SEM showed Figure 4 a, Figure 5 a and Figure 6 a.
[0043] Example 2
[0044] In a 250mL temperature-controlled reactor, 200mL of 2g / L sodium chloride solution was added as the electrolyte, and 1.0g of sodium acetate was added to the solution as a stabilizer. The cathode was a homemade platinum electrode (a platinum wire with a length of 20mm and a diameter of 1mm sealed in a quartz tube). The anode was a nickel-cobalt alloy sheet (the surface oxide film was polished with sandpaper, and then ultrasonically washed in anhydrous ethanol and deionized water for 10min each). In order to maintain the uniformity of the solution, the solution was continuously stirred at 120r / min with a magnetic stirrer. When the voltage was 500V, the current was 57mA, and the external resistance was 2kΩ, the solution temperature was maintained at 80℃, the cathode produced a glow, and a stable glow discharge plasma was formed. During the discharge process, the anode nickel-cobalt alloy sheet was continuously consumed, and a blue-green precipitate gradually appeared in the colorless solution. After continuous discharge for 1h, a blue-green NiCo-LDH product was obtained. The turbid solution was allowed to stand for 24 hours, then centrifuged at 10000 r / min for 10 minutes. The obtained product was washed with distilled water and anhydrous ethanol for several times to remove the electrolyte soluble salt, and finally vacuum dried at 60°C to constant weight and ground to obtain the target product. Its emission spectrum, solution pH change, infrared, XRD, SEM, and EDS were shown in Figure 2. Figure 2 , Figure 3 , Figure 4 b, Figure 5 b. Figure 6 b and Figure 7 .
[0045] Example 3
[0046] In a 250mL temperature-controlled reactor, 200mL of 2g / L sodium chloride solution was added as the electrolyte, and 1.5g of sodium acetate was added to the solution as a stabilizer. The cathode was a homemade platinum electrode (a platinum wire with a length of 20mm and a diameter of 1mm sealed in a quartz tube). The anode was a nickel-cobalt alloy sheet (sandpaper was used to remove the surface oxide film, and then ultrasonically washed in anhydrous ethanol and deionized water for 10min each). In order to maintain the uniformity of the solution, the solution was continuously stirred at 120r / min with a magnetic stirrer. When the voltage was 500V, the current was 55mA, and the external resistance was 2kΩ, the solution temperature was maintained at 80℃, the cathode produced a glow, and a stable glow discharge plasma was formed. During the discharge process, the anode nickel-cobalt alloy was continuously consumed, and a blue-green precipitate gradually appeared in the colorless solution. After continuous discharge for 1h, a blue-green NiCo-LDH product was obtained. The turbid solution was allowed to stand for 24 hours, then centrifuged at 9000 r / min for 10 minutes. The obtained product was washed with distilled water and anhydrous ethanol for several times to remove the electrolyte soluble salt, and finally vacuum dried at 60°C to constant weight and ground to obtain the target product. Its IR, XRD and SEM showed Figure 4 c, Figure 5 c and Figure 6 c.
[0047] (I) Preparation principle
[0048] 1. Spectral characteristics of CGDE
[0049] In order to explain the preparation mechanism of NiCo-LDH nanosheets, the emission spectrum of CGDE was measured by a fiber optic spectrometer. Figure 2 The typical emission spectrum of CGDE in the range of 200-1070 nm is shown. The emission lines at wavelengths of 283.0 and 309.0 nm are HO(A2∑ + →X2Π)((1,0) and (0.0)), the ion line of O II at 464.6nm, the H of hydrogen atom at 486.1nm and 656.1nm respectively. β and H α The spectral lines at 777.1nm and 844.7nm are the transition spectra of excited O atoms. This is because high-energy electrons excite vaporized water molecules to produce a large amount of HO·, H·, O·, and O 2- ·. The atomic lines of Na at 568.6, 589.0 and 819.2 nm are the Na atoms provided by the NaCl electrolyte. + caused by.
[0050] 2. Changes in solution pH during the preparation of NiCo-LDH
[0051] The relationship between the pH value of the solution and time during the discharge process was determined when the electrolyte was 200mL 2g / L sodium chloride and 1.0g sodium acetate was added to it. The results are shown in Figure 3 It can be seen that when preparing NiCo-LDH, the pH of the solution gradually increased from 7.73 to 9.43, indicating that the pH of the preparation of NiCo-LDH is alkaline.
[0052] 3. Mechanism of preparing NiCo-LDH by cathode glow discharge electrolytic plasma technology
[0053] Under the action of cathode glow discharge electrolytic plasma technology, the anode metal generates Ni through the anode dissolution process. 2+ ,Co 2+ During the liquid cathode glow discharge process, the H2O at the plasma-solution interface around the cathode is bombarded by high-energy electrons (e*) and decomposes into H·, e aq - and OH·, H2O2 and other active substances, among which H·, e aq - It is a reducing substance, while OH· and H2O2 are oxidizing substances.
[0054] Anode: Ni→Ni 2+ +2e-
[0055] Co→Co 2+ +2e -
[0056] The reactions produced by cathode glow discharge are as follows:
[0057] H2O+e*→H·+OH·
[0058] OH·+OH·→H2O2
[0059] H·+H·→H2
[0060] e - +OH·→OH - +H2O
[0061] e - +H·→OH - +H2
[0062] e - +H2O→OH - +H
[0063] e gas - +e gas - →2OH - +H2
[0064] 2H2O+2e gas - →H2+2OH -
[0065] The overall reaction for producing active species at the cathode is:
[0066] H2O+e*→H·+OH·+O·+H2O·+H2+O2+H2O2+OH -
[0067] Preparation mechanism of NiCo-LDH:
[0068] Ni produced at the anode 2+ 、Co 2+ Under the action of the electric field, it migrates to the cathode, and a large amount of active substances such as OH· and H2O2 are generated at the cathode plasma-liquid interface. These active substances undergo secondary reactions to produce OH - ;Co 2+ Reacts with OH· and H2O2 to generate Co 3+ . Then, OH - with Ni 2+ 、Co 2+ 、Co 3+NiCo-LDH was generated by coprecipitation reaction, and the reaction was as follows:
[0069] Co 2+ +OH·→Co 3+ +OH -
[0070] Co 2+ +H2O2→Co 3+ +OH -
[0071] Ni 2+ +Co 2+ +Co 3+ +n OH - →NiCo-LDH
[0072] This method has the characteristics of simple equipment, easy operation, mild conditions (no need for other gas protection), controllable reaction (one-step preparation, controlling the morphology of the material by controlling the influencing factors); the reaction process uses fewer types of chemical reagents (no additional reducing agents, oxidizing agents, alkali sources and metal precursor salts are required during the entire preparation process), reducing pollution to the environment; the product has high purity, is easy to separate, and can be produced on an industrial scale.
[0073] (II) Structural characterization of NiCo-LDH nanosheets
[0074] The structure and morphology of the material were characterized by infrared spectroscopy, X-ray powder diffraction and scanning electron microscopy.
[0075] 1. Infrared test
[0076] The Nexus 670 infrared spectrometer produced by Nicolet Company of the United States was used to analyze the –1 The nano-NiCo-LDH samples were characterized. Figure 4 The infrared spectrum of NiCo-LDH (a: 0.5 g CH3COONa, b: 1.0 g CH3COONa, c: 1.5 g CH3COONa), 3451 cm –1 The broad absorption peak at 1600 cm is attributed to the stretching vibration peak of the OH bond of adsorbed water in NiCo-LDH; –1 The absorption peaks at 1511 and 1390 cm-1 are attributed to the bending vibration peaks of OH; -1 The absorption peak at is CH3COO which enters the interlayer structure of LDH as an intercalated anion. - Asymmetric and symmetric stretching vibration peaks at 640 and 525 cm –1 A strong stretching vibration peak appears at , corresponding to the MO (Ni-O, Co-O) bond in the material, which preliminarily indicates that the target product prepared is NiCo-LDH.
[0077] 2. XRD test
[0078] The composition of the samples was determined using a RD / MAX-RB X-ray powder diffractometer (XRD) from Rigaku Corporation of Japan, using a Cu target (K α , λ=0.154056nm). Figure 5 XRD spectra of prepared NiCo-LDH (a: 0.5g CH3COONa, b: 1.0g CH3COONa, c: 1.5g CH3COONa). Three diffraction peaks are generated at 2θ=12.5°, 33.9°, and 60.5°, which correspond to the (003), (012), and (110) crystal planes of NiCo-LDH (JCPDS No.33-0429), respectively. Figure 5 It can also be seen that the diffraction peak of the prepared material NiCo-LDH has a lower peak intensity and a wider diffraction peak, indicating that the material has a lower degree of crystallinity and smaller grains; in addition, no other diffraction peaks are generated, indicating that the prepared sample has a high purity.
[0079] 3. Scanning electron microscope (SEM) test
[0080] The nano-NiCo-LDH was scanned using a plus FESEM scanning electron microscope from Zeiss, Germany, to observe the size and morphology of the sample. Before observation, the sample was vacuum dried at 60°C and then sprayed with gold. Figure 6 It can be seen from a that when 0.5 g of sodium acetate is added as a stabilizer, the NiCo-LDH nanosheets prepared by cathode glow discharge electrolysis are more evenly dispersed, and there are fewer disordered stacked nanosheets. Figure 6 b It can be seen that when 1.0 g of sodium acetate is added as a stabilizer, the NiCo-LDH nanosheets prepared by cathode glow discharge electrolysis are more evenly dispersed, with less agglomeration and less stacking between nanosheets. Figure 6 c It can be seen that when 1.5 g of sodium acetate is added, the NiCo-LDH nanosheets prepared by cathode glow discharge electrolysis are evenly dispersed, with less agglomeration, and curling appears at the edges of the nanosheets.
[0081] 4. Energy dispersive spectroscopy (EDS) analysis
[0082] Figure 7 This is an energy dispersion spectrum (EDS) diagram of the nano NiCo-LDH nanosheet provided by the present invention. It can be seen that the prepared sample mainly contains Ni, Co, O, and Cl elements.
Claims
1. A method for preparing layered nickel cobalt double hydroxide (NiCo-LDH) nanosheets, characterized in that: The steps include: Step 1: Use a high-voltage DC power supply to provide power, the cathode is a homemade platinum electrode, the anode is a nickel-cobalt alloy sheet, the electrolyte is a mixed solution of sodium chloride and sodium acetate, wherein sodium acetate is used as a stabilizer to control the morphology of NiCo-LDH, and a stabilizing resistor is added to the circuit; Step 2: Use a high-voltage DC power supply to apply a sufficiently high voltage between the two electrodes, so that the cathode platinum needle generates a tip discharge, thereby forming a stable glow; Step 3: The nickel-cobalt alloy sheet of the anode produces Ni in the solution through the anode dissolution process. 2+ and Co 2+ , the cathode plasma-liquid interface produces active species such as e aq - , H·, HO·, H2O2, and then a secondary reaction occurs to generate OH - ; Step 4: Use a magnetic stirrer to continuously stir and discharge for a period of time to obtain a blue-green turbid liquid; Step 5: Centrifuge the blue-green turbid liquid, wash it with distilled water and anhydrous ethanol for several times, dry it, and grind it to obtain a blue-green solid powder, which is NiCo-LDH.
2. The method for preparing NiCo-LDH nanosheets according to claim 1, characterized in that: In step 1, the electrolyte is 200 mL of 2 g / L sodium chloride solution, and the stabilizer is 0.5 to 1.5 g of sodium acetate added to 200 mL of the electrolyte.
3. The method for preparing NiCo-LDH nanosheets according to claim 1, characterized in that: In step 1, the cathode is a 20 mm long and 1 mm diameter platinum wire sealed in a quartz tube; the anode is a 6 cm long, 1 cm wide and 5 mm thick nickel-cobalt alloy sheet Ni50Co50; the positive and negative electrodes are inserted 3 cm below the liquid surface.
4. The method for preparing NiCo-LDH nanosheets according to claim 1, characterized in that: In step 1, the surface oxide film of the anode nickel-cobalt alloy sheet must be removed before use, usually by grinding it with 1000-grit sandpaper and then cleaning it with an ultrasonic cleaner.
5. The method for preparing NiCo-LDH nanosheets according to claim 1, characterized in that: In step 1, a 1-5 kΩ stabilizing resistor is connected between the negative electrode of the power supply and the cathode of the platinum needle.
6. The method for preparing NiCo-LDH nanosheets according to claim 1, characterized in that: In step 2, when the voltage is 500-550V and the current is 50-70mA, the cathode generates a tip discharge to form a stable plasma.
7. The method for preparing NiCo-LDH nanosheets according to claim 1, characterized in that: In step three, during the discharge process, the reaction temperature is maintained at 70-80°C.
8. The method for preparing NiCo-LDH nanosheets according to claim 1, characterized in that: In step 4, the magnetic stirrer continuously stirs the solution at 120-150 r / min to maintain the uniformity of the solution, and the glow discharge electrolysis is continued for 1.0 h.
9. The method for preparing NiCo-LDH nanosheets according to claim 1, characterized in that: In step 5, the speed of the centrifuge during sample processing is 8000-10000 r / min, and the sample is vacuum dried at 60°C.
